Effects of biodiesel fuel obtained from Salvia macrosiphon oil (ultrasonic-assisted) on performance and emissions of diesel engine. (15th July 2017) - Hoseini, S.S.; Najafi, G.; Ghobadian, B.; Rahimi, A.; Yusaf, Talal; Mamat, Rizalman; Sidik, N.A.C.; Azmi, W.H.
Abstract: The purpose of this study is to investigate the possibility of biodiesel production from Salvia macrosiphon oil (SMO) using the ultrasonic system. The major properties of Salvia macrosiphon methyl ester was compared with ASTM standards and the specifications met the requirements of biodiesel standards. This allows Salvia macrosiphon oil to be utilized for biodiesel production and be a potential substitute to diesel fuel; it can also be blended with diesel fuel. The performance and the exhaust emissions of a diesel engine operating on Salvia macrosiphon biodiesel-diesel blended fuels have been investigated. The experimental test results indicated that by using biodiesel-diesel blends, brake power, torque and concentrations of the CO2 and NOx emissions increased while the specific fuel consumption (SFC) and concentration of CO and HC emissions decreased. The results obtained revealed that high oxygen content of Salvia macrosiphon biodiesel resulted in significant overall improvements in the combustion reaction especially in B20 (20 vol% biodiesel and 80 vol% diesel fuel). CO and HC were reduced by up to 25% and 31.82% respectively in B20 compared to neat diesel fuel (B0). The innovated fuel blend also increased engine performances, which are the power and torque, by up to 18% and 15.8% respectively, and decreased specific fuel consumption by 4.6%. Highlights: Biodiesel produced from Salvia macrosiphon (SM) oil to evaluate the CI engine parameters. High oxygen content of SM biodiesel resulted in significant overall improvements in the combustion reaction. CO and HC were reduced by up to 25% and 31.82% respectively in B20 compared to B0. Power and torque increased up to 18% and 15.8% respectively with blended fuels. Specific fuel consumption decreased by 4.6% respectively in B20 compared to neat B0.